Day of the Week Effect in the Stock Markets of Fragile Five Countries After 2008 Global Financial Crisis - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
In this study, it is analyzed the existence of day of the week effect in the stock markets of Brazil, India, Indonesia, Turkey and South Africa which are named as fragile five countries (BIITS). To determine this effect in fragile five countries; daily closing price data of basic indices of the stock markets of these countries' for the period (2 January 2009-31 December 2015) and Kruskal-Wallis test and Wilcoxon rank sum test which are non-parametric statistical analysis methods, are used. The results obtained in this study supports the literature findings that day of the week effect is reducing in developed and emerging markets in the recent years for fragile five countries for the period after the 2008 global financial crisis. The findings indicate that, except Indonesia, day of the week effect doesn't exist in other four countries' stock markets. In Indonesia stock market, the lowest return is on Monday, highest return is on Wednesday.
Keywords: OF-THE-WEEK; RETURNS; SEASONALITY; ROBUSTNESS